Assessment of genetic diversity using microsatellite markers to compare donkeys () with horses () - Su Min Kim (Animal Bioscience, 2021)
Objective The study aimed to evaluate the diversity of donkey populations by comparing with the diversity of Thoroughbred and Jeju Halla horses; identified breeding backgrounds can contribute to management and conservation of donkeys in South Korea. Methods A total of 100 horse (50 Thoroughbreds and 50 Jeju Halla horses) and 79 donkeys samples were genotyped with 15 microsatellite markers (AHT4, AHT5, ASB2, ASB17, ASB23, CA425, HMS1, HMS2, HMS3, HMS6, HMS7, HTG4, HTG10, LEX3, and VHL20), to identify genetic diversity and relationships among horses and donkeys. Results The observed number of alleles per locus ranged from 1 (ASB17, HMS1) to 14 (AHT5), with a mean value of 4.87, 8.00, and 5.87 in Thoroughbreds, Jeju Halla horses, and donkeys, respectively. Of the 15 markers, AHT4, AHT5, ASB23, CA425, HMS2, HMS3, HTG4, HTG10, and LEX3 loci had relatively high polymorphism information content (PIC) values (PIC>0.5) in these three populations. Mean levels of genetic variation were HE = 0.6721 and HO = 0.6600 in Thoroughbreds, HE = 0.7898 and HO = 0.7100 in Jeju Halla horses, and HE = 0.5635 and HO = 0.4861 in donkeys. Of the 15 loci in donkeys, three loci had negative inbreeding coefficients (FIS), with a moderate mean FIS (0.138). The FIS estimate for the HTG4 marker was highest (0.531) and HMS6 marker was lowest (−0.001). The total probability of exclusion value of 15 microsatellite loci was 0.9996 in donkeys. Conclusion Genetic cluster analysis showed that the genetic relationship among 79 donkeys was generally consistent with pedigree records. Among the three breeds, donkeys and Thoroughbred horses formed clearly different groups, but the group of Jeju Halla horses overlapped with that of Thoroughbred horses, suggesting that the loci would be suitable for donkey parentage testing. Therefore, the results of this study are a valid tool for genetic study and conservation of donkeys.